Doing Qualitative Research - Crabtree, Benjamin F.; Miller, William L. (William Lloyd), 1949- (California : Sage Publications, Inc., 1999)
This completely revised and greatly expanded edition of Doing Qualitative Research spans the spectrum of primary care research illustrating when methods are appropriate and how to use them.
Clinical research: a multimethod typology and qualitative roadmap / William L. Miller and Benjamin F. Crabtree -- Sampling in qualitative inquiry / Anton J. Kuzel -- Participant observation / Stephen P. Bogdewic -- Key informant interviews / Valerie J. Gilchrist and Robert L. Williams -- Depth interviewing / William L. Miller & Benjamin F. Crabtree -- The use of focus groups in clinical research / Judith Belle Brown -- The dance of interpretation / William L. Miller and Benjamin F. Crabtree -- A grounded hermeneutic editing approach / Richard B. Addison -- Using codes and code manuals: a template organizing style of interpretation / Benjamin F. Crabtree and William L. Miller -- Immersion/crystallization / Jeffrey Borkan -- Data management and interpretation using computers to assist / Lynn M. Meadows and Diane M. Dodendorf -- Narrative approaches to qualitative research in primary care / Jessica H. Muller -- Using videotapes in qualitative research / Virginia Elderkin-Thompson and Howard Waitzkin -- An armchair adventure in case study research / Virginia A. Aita and Helen E. McIlvain -- Participatory inquiry / Janecke Thesen and Anton J. Kuzel -- Researching practice settings : a case study approach / Benjamin F. Crabtree and William L. Miller -- Making changes with key questions in medical practices: studying what makes a difference / Kirsti Malterud -- Standards of qualitative research / Richard M. Frankel -- Qualitative research: perspectives on the future / Lucy M. Candib, Kurt C. Stange, and Wendy Levinson.
Includes bibliographical references (p. 363-390) and index.
Keywords: Primary care (Medicine) -- Research -- Methodology; Social medicine -- Research -- Methodology; Social sciences -- Research -- Methodology; Qualitative research; Primary Health Care [MESH]; Research [MESH]; Social Medicine [MESH]; Social Sciences [MESH]; Data Collection [MESH]; Primary care (Medicine); Primary care (Medicine) -- Methodology; Social Medicine; Research; Social Medicine -- methods; Social Sciences; Social Sciences -- methods; Research Design; Primary Health Care